Effects Of Emotions Based Mobile Messages On The Performance, Attitude And Motivation Among Malaysian Students Learning Arabic - Alsalem Alali, Mokaram Kaled (2014)
The purpose of this study was to investigate the effects of using emotions based mobile messages on performance, attitude and motivation among Malaysian students learning Arabic. One independent variable was the types of messages: emotion based mobile message (EBMM) and non-emotion based mobile message (NEBMM). The dependent variables were performance, attitude and motivation, while the moderating variable was gender. The study sample consisted of 132 Malaysian college students who were randomly selected from Kolej Islam Teknologi Antarabangsa. Analyses of covariance (ANCOV A) and t-test were carried out to examine the main effects as well as the interaction effects of the independent variable on dependent variables. The findings of this study showed that students